ChemInform Abstract: Palladium‐Catalyzed Direct ortho‐Nitration of Azoarenes Using NO2 as Nitro Source. Issue 10 (March 2015) - Dong, Jiawei; Jin, Bo; Sun, Peipei
Abstract A direct ortho‐nitration of a variety of azoarenes is achieved with NO2 as nitro source in the presence of Pd(OAc)2 as catalyst.